Cretaceous Blind Snake from Brazil Fills Major Gap in Snake Evolution - Fachini, Thiago Schineider (iScience, 2020)
Blind snakes (Scolecophidia) are minute cryptic snakes that diverged at the base of the evolutionary radiation of modern snakes. They have a scant fossil record, which dates back to the Upper Paleocene-Lower Eocene (∼56 Ma); this late appearance conflicts with molecular evidence, which suggests a much older origin for the group (during the Mesozoic: 160–125 Ma). Here we report a typhlopoid blind snake from the Late Cretaceous of Brazil, Boipeba tayasuensis gen. et sp. nov, which extends the scolecophidian fossil record into the Mesozoic and reduces the fossil gap predicted by molecular data. The new species is estimated to have been over 1 m long, much larger than typical modern scolecophidians (<30 cm). This finding sheds light on the early evolution of blind snakes, supports the hypothesis of a Gondwanan origin for the Typhlopoidea, and indicates that early scolecophidians had large body size, and only later underwent miniaturization.